COMPARATIVE ANALYSIS OF J. BYRON AND M. LERMONTOV’S POETRY - Ruzibayeva, Aziza (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article provides a comparative analysis of the poetry of two prominent Romantic-era poets, Lord Byron and Mikhail Lermontov. By examining their works in terms of themes, style, and influences, this study aims to highlight the similarities and differences between these two poets and explore how their poetry reflects the social and cultural contexts of their respective nations.